2020
DOI: 10.18203/issn.2454-5929.ijohns20203503
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to assess the efficacy of fluticasone and mometasone in allergic rhinitis

Abstract: <p class="abstract"><strong>Background:</strong> Allergic rhinitis is the most prevalent of allergic diseases in the world. Pharmacotherapy remains the mainstay of treatment.  Nasal corticosteroids being the most applicable drugs for its treatment. The objective of this study was to compare the efficacy of fluticasone propionate (FP) and mometasone furoate (MF) nasal sprays in the treatment of allergic rhinitis based on total nasal symptom score (TNSS) questionnaire.</p><p class="abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
1
0
0
Order By: Relevance
“…It was inferred that mometasone furoate had better efficacy in relieving inflammatory symptoms of rhinitis as compared to fluticasone. 16 In the present study, more number of patients had shown remarkable improvement and greater reduction in severity of the disease. This can be attributed to better anti-inflammatory effect of mometasone furoate.…”
Section: Discussionsupporting
confidence: 54%
“…It was inferred that mometasone furoate had better efficacy in relieving inflammatory symptoms of rhinitis as compared to fluticasone. 16 In the present study, more number of patients had shown remarkable improvement and greater reduction in severity of the disease. This can be attributed to better anti-inflammatory effect of mometasone furoate.…”
Section: Discussionsupporting
confidence: 54%